1986
DOI: 10.1029/ja091ia09p09923
|View full text |Cite
|
Sign up to set email alerts
|

Star of Lima: Overview and Optical Diagnostics of a Barium Alfvén Critical Velocity Experiment

Abstract: The Alfvén critical velocity mechanism for ionization of a neutral gas streaming across the magnetic field has been demonstrated in laboratory experiments. In March 1983, two rocket‐borne experiments with Ba and Sr tested the effect in the wall‐less laboratory of space from Punto Lobos, Peru, near 430 km altitude. “Star of Lima” used a conical Ba shaped charge aimed at an instrument payload about 2 km away. Because of rocket overperformance the detonation occurred in partial sunlight, so that less than 21.6% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Thus, from the available information it appears that the ions acquire additional energy only when injected at large angles to the magnetic field. The existence or nonexistence of critical velocity ionization effects in high-velocity barium releases has been controversial [e.g., Haerendel, 1982' Wescott et al, 1986. Independent of the critical velocity question a variety of releases [e.g., Rieger et al, 1970' Heppner et al, 1981 have indicated that the shortest, and most recently, determined theoretical characteristic time for barium photoionization, 28 _+ 6 s [Carlsten, 1975], is long relative to observed values.…”
Section: High-velocity Ray Characteristicsmentioning
confidence: 99%
“…Thus, from the available information it appears that the ions acquire additional energy only when injected at large angles to the magnetic field. The existence or nonexistence of critical velocity ionization effects in high-velocity barium releases has been controversial [e.g., Haerendel, 1982' Wescott et al, 1986. Independent of the critical velocity question a variety of releases [e.g., Rieger et al, 1970' Heppner et al, 1981 have indicated that the shortest, and most recently, determined theoretical characteristic time for barium photoionization, 28 _+ 6 s [Carlsten, 1975], is long relative to observed values.…”
Section: High-velocity Ray Characteristicsmentioning
confidence: 99%
“…In light of the negative or inconclusive results reported recently from space-based CIV experiments [Haerendel, 1982;Torbert, 1988;Wescott et al, 1986;Hallinan, 1988] in comparison with the success of the previously mentioned laboratory experiments, it is clear that a variety of factors besides the threshold velocity V, affect whether or not a CIV discharge will occur. Since there would be important consequences if CIV were to occur in the interaction of spacecraft with the near space environment , it is important to understand the underlying mechanisms at work in CIV for predictive purposes.…”
Section: Introductionmentioning
confidence: 98%
“…Upper ionospheric barium release using sounding rockets to test Alfv6n's critical ionization velocity hypothesis (1954) has been conducted actively more than a half dozen times over the last decade [e.g., Haerendel, 1982;Wescott et al, 1986;Wescott et al, 1990; Stenbaek-Nielsen et al, 1990a, b; Totbert et al, 1992]. According to Alfv6n's critical ionization velocity (CIV) hypothesis, a rapid gas ionization will occur when a neutral gas cloud moves across a magnetized plasma with a relative velocity perpendicular to the magnetic field exceeding a critical value, vc, defined by V/2eqJion/M, where (•ion and M are the ionization potential and mass of neutral atom, respectively.…”
Section: Introductionmentioning
confidence: 99%